Advances in porous inorganic nanomaterials for bone regeneration - Huan Dai; Sepanta Hosseinpour; Shu Hua; Chun Xu (Nano TransMed)
ABSTRACT: Porous inorganic materials such as mesoporous silica nanoparticles (MSNs), mesoporous bioactive glasses (MBGs), porous calcium phosphates, and metal-organic frameworks (MOFs) are used for bone regeneration due to their osteoinductive and porous properties. The direct osteogenesis ability can be adjusted by the design and composition of those inorganic materials. With porous structure, adjustable pore size and high surface area, they are used as carriers to deliver various small molecular drugs, proteins, and genes locally to promote bone generation. The surface of those porous inorganic materials can be further functionalized to control the loading and release of drugs and modulate the behaviour of host cells. This review summarizes the recent advances of various porous inorganic nanomaterials for bone repairing with a focus on their performance as scaffolds and drug delivery systems. We also discuss the challenges and prospects of porous inorganic nanomaterials for the future clinical application for bone regeneration.